2009
DOI: 10.1542/peds.2007-2850
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Transfusion Practices Among Neonatologists in the United States and Canada: Results of a Survey

Abstract: There is great variability in platelet transfusion practices among US and Canadian neonatologists, suggesting clinical equipoise in many clinical scenarios. Prospective randomized clinical trials to generate evidence-based neonatal platelet transfusion guidelines are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
94
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(102 citation statements)
references
References 35 publications
4
94
0
4
Order By: Relevance
“…Published surveys concerning blood transfusion practices and policies for Canadian paediatric patients indicate that, for neonates, a minority of centres use washed or volume-reduced red blood cell units and approximately one-half use volume-reduced platelets (40)(41)(42)(43). Adoption of these practices could possibly contribute to a lower incidence of TRALI in neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Published surveys concerning blood transfusion practices and policies for Canadian paediatric patients indicate that, for neonates, a minority of centres use washed or volume-reduced red blood cell units and approximately one-half use volume-reduced platelets (40)(41)(42)(43). Adoption of these practices could possibly contribute to a lower incidence of TRALI in neonates.…”
Section: Discussionmentioning
confidence: 99%
“…<50,000/µl). Platelet transfusion is recommended for any neonate with active bleeding and a platelet count <100,000/µl (33,34). For neonates who are treated by extracorporeal membrane oxygenation and those requiring major surgery, most centers advocate keeping the platelet count >100.000/µl (28).…”
Section: Indicationsmentioning
confidence: 99%
“…When only a subset of extremely low birthweight neonates (<1000 g at delivery) were considered, 73% had one or more platelet counts below 150,000/µl [3]. Among all thrombocytopenic preterm neonates, 25-38% will have blood platelet counts less than 50,000/µl (i.e., severe thrombocyto penia) and will probably receive PTXs [3][4][5]. Thus, between 2 and 8% of all preterm neonates admitted to an NICU will receive a PTX [5], with extremely low birthweight neonates given PTX much more frequently (45% in one report [3]).…”
Section: Guidelines For Neonatal Ptxsmentioning
confidence: 99%
“…Since only one randomized controlled trial studying PTXs in preterm neonates has been reported [6], the practice of neonatal PTXs is based almost entirely on 'level 4 evidence' (i.e., expert opinion and reasoning), and practices vary widely [5]. Andrew et al's randomized clinical trial enrolled preterm neonates during the first week of life and assigned them to either a group in which PTXs were given liberally to keep the blood platelet count within the normal range (i.e., to receive a PTX whenever the blood platelet count fell below 150,000/µl), or a group that received a PTX for specific reasons related to true thrombocytopenia (i.e., clinical concern about bleeding or whenever the blood platelet count fell below 50,000/ µl) [6].…”
Section: Guidelines For Neonatal Ptxsmentioning
confidence: 99%
See 1 more Smart Citation